A retrospective descriptive study characterizing coronavirus disease epidemiology among people in the Kurdistan Region, Iraq - Nawfal R Hussein; Ibrahim A Naqid; Zana Sidiq M. Saleem (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract